2018
DOI: 10.1111/imm.12907
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin ameliorates collagen‐induced arthritis via suppressing nuclear factor‐κB signalling pathway in osteoclast differentiation

Abstract: Paeoniflorin (PF), extracted from the root of Paeonia lactiflora Pall, exhibits anti-inflammatory properties in several autoimmune diseases. Osteoclast, the only somatic cell with bone resorbing capacity, was the direct cause of bone destruction in rheumatoid arthritis (RA) and its mouse model, collagen-induced arthritis (CIA). The objective of this study was to estimate the effect of PF on CIA mice, and explore the mechanism of PF in bone destruction. We demonstrated that PF treatment significantly ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Radix Paeoniae alba has been widely used in traditional Chinese medicine since ancient times. As the main component of Radix Paeoniae alba , PF was chosen for its outstanding antiinflammatory effects (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Radix Paeoniae alba has been widely used in traditional Chinese medicine since ancient times. As the main component of Radix Paeoniae alba , PF was chosen for its outstanding antiinflammatory effects (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferulic acid promotes osteogenesis in bone marrow mesenchymal stem cells and suppresses osteoclast differentiation (Du et al, 2017; Doss et al, 2018). Paeoniflorin has a significant anti-inflammatory effect on rheumatoid arthritis (Lai et al, 2018; Xu et al, 2018). Paeoniflorin also shows antiosteoporosis activity and regulates osteoclastogenesis and osteoblastogenesis (Li and Chent 2018b; Wang et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating investigations have indicated that osteoblasts and osteoclasts can interact through RANKL/ RANK/OPG system to mediate bone modelling and remodeling [20,21], and the relative expression and the balance between RANKL and OPG in osteoblasts can determine the mass and strength of bone, which means the upregulated OPG/RANKL ratio could prevent osteoclastogenesis [22][23][24][25]. Although the detailed mechanism is unknown, the up-regulated OPG, RANK, and RANKL in the necrotic femoral head can be reversed by IL-15 deficiency.…”
Section: Discussionmentioning
confidence: 99%